Cytotaxonomical Notes on Two Nepalese Varieties of Desmodium heterocarpon (L.) DC. - Manandhar, Laxmi; Shakya, Shyam Ratna (Journal of Natural History Museum, 2009)
The paper deals with cytotaxonomical accounts of the two varieties of Desmodium heterocarpon (L.) DC such as var. strigosum and var. heterocarpon collected from Nepal. Somatic chromosome number of both the varieties was found to be 2n=22. Smaller chromosomes with median constrictions predominated in both the cases. The slight differences in relative and absolute lengths between the karyotypes of the two varieties have been recorded.Key word: Varieties; Cytological analysis; Camera lucida; Abnormal stucture.Journal of Natural History Museum Vol. 24, 2009 Page:  130-136